Competitive cross‐subsidization. (10th July 2019) - Chen, Zhijun; Rey, Patrick
Abstract: Cross‐subsidization arises naturally when firms with different comparative advantages compete for consumers with heterogeneous shopping patterns. Firms then face a form of co‐opetition, as they offer substitutes for one‐stop shoppers and complements for multi‐stop shoppers. When intense competition for one‐stop shoppers drives total prices down to cost, firms subsidize weak products with the profits made on strong products. Moreover, firms have incentives to seek comparative advantages on different products. Finally, banning below‐cost pricing increases firms' profits at the expense of one‐stop shoppers, which calls for a cautious use of below‐cost pricing regulations in competitive markets.